Pemahaman Materi PAI dan Implikasinya Terhadap Kemudahan Mengamalkan Nilai-Nilai Agama di SMP Negeri 3 Limboto Barat Kabupaten Gorontalo - Danial, Moh Ramli; Petta Solong, Najamuddin; Datunsolang, Rinaldi (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study aims to determine students' understanding of Islamic Religious Education (IRE) material and its implications for the ease of practicing religious values among students at SMP Negeri 3 Limboto Barat. The approach used in this study is descriptive qualitative, with data collection techniques including observation, interviews, and documentation. The results of the study indicate that students' understanding of IRE material is quite good, particularly in aspects of worship they experience in their daily lives, such as prayer and fasting. IRC teachers play a central role in the learning process by applying interactive methods, hands-on practice, and setting a good example. The implications of this understanding are evident in students' practice of religious values, such as increased awareness of performing Dhuha prayer and congregational prayer voluntarily, as well as their active participation in religious activities at school. Supporting factors in PAI learning include the role of teachers as role models, adequate school facilities, and parental involvement. The inhibiting factors are time constraints, differences in students' learning styles, and a lack of support from the environment outside of school. However, teachers are able to overcome these obstacles with creative and adaptive learning strategies.